The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1108/wje-08-2021-0478
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of bending soft pneumatic network actuators for various designs using the finite element method

Abstract: Purpose This paper aims to present the numerical analysis of displacements, forces and bend angles of three different structural designs of a soft actuator using the finite element method. The results of this analysis help understand the physical behavior of the soft pneumatic actuator. Design/methodology/approach The soft actuator is designed using commercial modeling software, and the design of the actuator is analyzed using ABAQUS 19.0 with a standard implicit nonlinear analysis. There are three types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As the material selected is hyperelastic in nature, a mathematical model, Yeoh model (second order), was used to fully describe the material model (Polygerinos et al , 2013; Yeoh, 1993; Li and Wei, 2015; Rackl, 2015) as shown in equation (1), where W is the strain-energy potential, I 1 is the first invariant of the right Cauchy–Green tensor and C i are the material constants. The modulus of elasticity is not compatible with hyperelastic materials (Venkatesan et al , 2021b), and the material coefficients of Yeoh model used are listed in Table 1 which describes the nonlinear stress–strain behavior of the material (Xavier et al , 2021; Venkatesan et al , 2021a): …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the material selected is hyperelastic in nature, a mathematical model, Yeoh model (second order), was used to fully describe the material model (Polygerinos et al , 2013; Yeoh, 1993; Li and Wei, 2015; Rackl, 2015) as shown in equation (1), where W is the strain-energy potential, I 1 is the first invariant of the right Cauchy–Green tensor and C i are the material constants. The modulus of elasticity is not compatible with hyperelastic materials (Venkatesan et al , 2021b), and the material coefficients of Yeoh model used are listed in Table 1 which describes the nonlinear stress–strain behavior of the material (Xavier et al , 2021; Venkatesan et al , 2021a): …”
Section: Methodsmentioning
confidence: 99%
“…In real-world scenario, the pneumatic chambers are connected to a source via a controller that regulates supply pressure in these chambers. The assumption made in the finite element method model is that bottom face of the actuator was constrained in all directions to simulate this fixation, and the other end was allowed to bend freely (Venkatesan et al , 2021a, 2021b). The effect of gravity was not considered in the present study, and only a static finite element analysis of the actuator is carried out.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluid-powered fibre-reinforced actuators [21] have been devised, mirroring the intricate movements of the index finger and thumb. Numerous researchers [22][23][24][25][26][27][28][29][30][31][32][33][34][35] have made significant contributions in various areas, showcasing their remarkable work.…”
Section: Introductionmentioning
confidence: 99%